Cooking Class Activities: Fostering Independence and Building Self-Confidence in Early Childhood - Anak Agung Ari Laksemi (Al-Qalam Institute, 2024)
Learning innovation is very important because it can provide fun and meaningful learning experiences for young children. Cooking class activities in ECE are one application of Project Learning, which is an implementation of the Independent Curriculum that involves children actively in the learning process. This qualitative research aims to discover how ECE teachers design cooking class activities, how students are involved during the activity, and what aspects of development young children achieve through this activity. The research was conducted at the Open Flow Learning Centre, Badung, Bali, using observation, interviews, and documentation methods for 4 ECE teachers and twelve students (three boys and nine girls). Through observations, it was found that cooking class activities at this institution are unique because they involve students from collecting ingredients to handling leftover ingredients that are not used. It was also observed that children had independence and self-confidence when carrying out activities. Considering the many benefits children get from cooking class activities, it is hoped that ECE teachers in other institutions can implement this activity to maximize children's involvement and development.